Camouflage versus running performance as strategies against predation in a lizard inhabiting different habitats. Issue 23 (20th November 2021) - Wan, Lixia; Liu, Zhenxia; Wang, Tao; Yang, Minglu; Li, Jiasheng; Sun, Hui; Niu, Chenkai; Zhao, Wei; Jin, Yuanting
Abstract: Running speed and camouflage are associated with the foraging and anti‐predator abilities of animals. The toad‐headed lizard, Phrynocephalus versicolor, has evolved a darker dorsal color in melanistic habitats and maintained a lighter color in adjacent, non‐melanistic habitats. We test the hypothesis that lizards have weaker running speed on well‐matching backgrounds than on less matching backgrounds. We used lizard models to compare the predation pressure, while the running speed of dark and light lizards were compared in field tunnels using a video recording method. Our results indicated that both the dark lizards in melanistic Heishankou (HSK) and the light lizards in non‐melanistic Guazhou (GZ) face lower predation pressure than potential color‐background unmatched lizards. The light lizards have a potentially higher running speed than darker lizards in melanistic habitats, which implies that substrate color matching populations with benefits of camouflage might have lower anti‐predation pressure, and the costs of investment in melanin production may reduce running capacity. Abstract : The lizards with substrate matching dorsal color have lower predation pressure than substrate unmatched lizards. The dark lizards with benefits of camouflage lowed the running speed in melanistic habitat.